General parenting and mothers' snack giving behavior to their children aged 2–7. (October 2020) - Damen, Femke W.M.; Steenbekkers, Bea L.P.A.; de Vaal, Marielle T.; Kampen, Jarl K.; Fogliano, Vincenzo; Luning, Pieternel A.
Highlights: Mothers differed significantly on scores for coercive control and overprotection. When mothers scored higher on coercive control, more of them provided unhealthy snacks. When mothers scored higher on coercive control, fewer of them provided vegetables. Abstract: The increasing intake of energy-dense snacks among children is one of the contributing factors to childhood overweight. To understand children's snacking habits, snack choices of parents are essential to take into account. General parenting is one of the important factors that can influence the development of healthy eating patterns and weight status among children. Therefore, this study aims to explore how the key constructs of general parenting (nurturance, structure, behavioral control, overprotection and coercive control) relate to mothers' snack choice for their children aged 2–7 years. The Dutch version of the validated Comprehensive General Parenting Questionnaire (CGPQ) was used to assess the key constructs of general parenting. An extensive, 13-day diary study with 136 Dutch mothers was used to measure the snacks mothers provided their children aged 2–4 years and 5–7 years. For both groups of mothers in our sample, differences were found on the scores of coercive control and overprotection. No differences between the mothers were present on the key constructs behavioral control, nurturance, and structure. Results give a first indication that more mothers who scored relatively higher on coercive control provided unhealthy products, like candy and cookies, and fewer mothers provided vegetables, compared to mothers who scored lower on coercive control. A higher score on coercive control combined with a higher score on overprotection was associated with fewer mothers providing unhealthy products like cookies and candies.